2017
DOI: 10.1136/bjsports-2017-097659
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular tendon involvement on MRI has limited value for predicting time to return to play following acute hamstring injury

Abstract: Time to RTP for injuries with full-thickness disruption of the intramuscular tendon and waviness is significantly longer (by slightly more than 1 week) compared with injuries without intramuscular tendon involvement. However, due to the considerable overlap in time to RTP between groups with and without intramuscular tendon involvement, its clinical significance for the individual athlete is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 27 publications
2
53
2
5
Order By: Relevance
“…Our previous work demonstrated that full-thickness intramuscular tendon disruption and presence of waviness were associated with a delay in RTP by 8–9 days 10. Yet, based on considerable within-group variance and substantial between-group overlap, we concluded that the contribution of intramuscular tendon injury to RTP prediction, and therefore its prognostic value, was limited.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our previous work demonstrated that full-thickness intramuscular tendon disruption and presence of waviness were associated with a delay in RTP by 8–9 days 10. Yet, based on considerable within-group variance and substantial between-group overlap, we concluded that the contribution of intramuscular tendon injury to RTP prediction, and therefore its prognostic value, was limited.…”
Section: Discussionmentioning
confidence: 79%
“…We recently showed that hamstring muscle injury with intramuscular tendon injury was associated with longer time to RTP (by slightly more than a week) 10. Unfortunately, there was inadequate power to analyse reinjuries.…”
Section: Introductionmentioning
confidence: 99%
“…La rehabilitación y recuperación de las lesiones musculares en isquiosurales tiene como objetivo devolver al jugador a su nivel de rendimiento anterior a la lesión en el menor tiempo posible, minimizando al mismo tiempo el riesgo de volver a lesionarse (Lalín & Peirau, 2011). Este aspecto es altamente importante ya que la tasa de reincidencia de este tipo de lesiones es alta (16%-22%) (Petersen, Thorborg, Nielsen, Budtz-Jørgensen, & Hölmich, 2011;Pollock et al, 2016) y está relacionada con un tiempo significativamente mayor para el regreso a la competición (Ekstrand, Hagglund, & Walden, 2011;Van der Made et al, 2017).…”
Section: Justificaciónunclassified
“…Respecto a la vuelta a la competición tras sufrir una rotura muscular de los isquiosurales, son varios los estudios que registraron el tiempo de recuperación (Hallén & Ekstrand, 2014a;Stares et al, 2018;Van der Made et al, 2017) donde los datos reportados indicaron una media de 24±9,7 días desde que se produce la lesión hasta que el jugador vuelve a competir. Si bien algunos se realizaron con estudiantes (Kilcoyne, Dickens, Keblish, Rue, & Chronister, 2011).…”
Section: Justificaciónunclassified
See 1 more Smart Citation